2017
DOI: 10.1186/s13075-017-1360-7
|View full text |Cite
|
Sign up to set email alerts
|

Limited cutaneous systemic sclerosis skin demonstrates distinct molecular subsets separated by a cardiovascular development gene expression signature

Abstract: BackgroundSystemic sclerosis (SSc; scleroderma) is an uncommon autoimmune rheumatic disease characterised by autoimmunity, vasculopathy and fibrosis. Gene expression profiling distinguishes scleroderma from normal skin, and can detect different subsets of disease, with potential to identify prognostic biomarkers of organ involvement or response to therapy. We have performed gene expression profiling in skin samples from patients with limited cutaneous SSc (lcSSc).MethodsTotal RNA was extracted from clinically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…In our study, the GO term analysis results indicated that the downregulated DEGs were mainly enriched in response to wounding, regulation of cell proliferation, blood vessel morphogenesis, cytokine activity, and extracellular matrix, and the upregulated DEGs were significantly enriched in multicellular organismal metabolic process, cell division, cell cycle phase, metalloendopeptidase activity, and spindle. Response to wounding means a change in the state or activity of a cell or a stimulus indicating damage to the organism, which is closely related to the occurrence and development of various diseases 18-20. Dysfunction of the regulation of cell proliferation, blood vessel morphogenesis, cell division and cell cycle are critical causes of tumorigenesis and cancer progression 21-23.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the GO term analysis results indicated that the downregulated DEGs were mainly enriched in response to wounding, regulation of cell proliferation, blood vessel morphogenesis, cytokine activity, and extracellular matrix, and the upregulated DEGs were significantly enriched in multicellular organismal metabolic process, cell division, cell cycle phase, metalloendopeptidase activity, and spindle. Response to wounding means a change in the state or activity of a cell or a stimulus indicating damage to the organism, which is closely related to the occurrence and development of various diseases 18-20. Dysfunction of the regulation of cell proliferation, blood vessel morphogenesis, cell division and cell cycle are critical causes of tumorigenesis and cancer progression 21-23.…”
Section: Discussionmentioning
confidence: 99%
“…The 28 genes and promoters identified in this study (Table 2) were compared to results from published genome-wide DNA methylation [13] and gene expression studies [39][40][41][42][43][44][45][46][47][48][49] in cultured dermal fibroblasts or skin biopsies. Of our top genes and promoters, two CpGs in distal-less homeobox 5 (DLX5) were reported as hypermethylated in skin fibroblasts from dcSSc patients [13], which is consistent with our results.…”
Section: Comparison Of Dna Methylation With Previous Reports In Dermal Tissuesmentioning
confidence: 99%
“…Gene expression profiling of the whole transcriptome is increasingly being used to explore disease-related genes and enable disease classification and clinical prediction (5,6). Derrett-Smith et al (7) conducted gene expression profiling analysis of unaffected skin obtained from patients with localized cutaneous systemic sclerosis (lcSSc). The results showed that the differentially expressed genes (DEGs) are related to cardiovascular system and mainly enriched in fibrotic signaling pathways.…”
Section: Introductionmentioning
confidence: 99%